Characterizing oxygen atoms in perovskite and pyrochlore oxides using ADF-STEM at a resolution of a few tens of picometers. (15th April 2021) - Mostaed, Ali; Walkley, Brant; Hatnean, Monica Ciomaga; Balakrishnan, Geetha; Lees, Martin R.; Beanland, Richard; Sinclair, Derek C.; Reaney, Ian M.
Abstract: We present an aberration corrected scanning transmission electron microscopy (ac-STEM) analysis of perovskite (LaFeO3 ) and pyrochlore (Yb2 Ti2 O7 and Pr2 Zr2 O7 ) oxides and demonstrate that both the shape and contrast of visible atomic columns in annular dark-field (ADF) images are sensitive to the presence of nearby atoms of low atomic number (e.g. oxygen). We show that point defects (e.g. oxygen vacancies), which are invisible – or difficult to observe due to limited sensitivity – in x-ray and neutron diffraction measurements, are the origin of the complex magnetic ground state of pyrochlore oxides. In addition, we present a method by which light atoms can be resolved in the quantitative ADF-STEM images. Using this method, we resolved oxygen atoms in perovskite and pyrochlore oxides and propose this method to be suitable for other materials containing both light and heavy elements. Graphical abstract: Image, graphical abstract